2018
DOI: 10.5152/ejbh.2018.4170
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Subtype Distribution in Inflammatory Breast Cancer Outcome

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Additionally, patients with unknown biologic subtype were excluded in the SEER analysis. Nonetheless, this study reported poor survival for patients with TN-IBC, which is consistent with our report and other studies in the literature [24,53,54,55].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, patients with unknown biologic subtype were excluded in the SEER analysis. Nonetheless, this study reported poor survival for patients with TN-IBC, which is consistent with our report and other studies in the literature [24,53,54,55].…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to a recent study of 7304 women with non-metastatic IBC, wherein radiotherapy was associated with improved 5-year survival (adjusted HR = 0.64, 95% CI 0.61–0.69) [69]. Nonetheless, a multidisciplinary multimodal approach consisting of NACT followed by surgery and post-mastectomy radiation has been underutilized in previous reports of IBC [55,70].…”
Section: Discussionsupporting
confidence: 85%
“…In stage IV disease, the median OS is 2.27 years in IBC patients versus 3.40 years in non-IBC patients [7,8]. Although IBC, like non-IBC breast cancers, is a heterogeneous disease and can occur as any of the four molecular subtypes, it is most commonly either human epidermal growth factor receptor 2 (HER2) overexpressive or triple negative (TN) [9,10]. TN breast cancer, which is defined by the absence of estrogen and progesterone receptors, and a lack of HER2 overexpression, has a poorer prognosis than other subtypes [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, prognostic stage IIIC, which included (1) ER+/PR−/HER2−/grade 3, (2) ER−/PR+/HER2−/grade 3, and (3) triple-negative IBC, had significantly worse prognoses than other stages in both cohorts. Six previous studies investigating the relationship between subtypes and survival outcomes in IBC have reported that triple-negative IBC has the worst survival outcomes [ 9 , 10 , 11 , 12 , 13 , 14 ]. These studies supported our findings that IBC’s prognostic stage IIIC has a poor prognosis because the triple-negative type is the major component of prognostic stage IIIC.…”
Section: Discussionmentioning
confidence: 99%